2021
DOI: 10.2147/prbm.s329036
|View full text |Cite
|
Sign up to set email alerts
|

Personality Profiles and Personal Factors Associated with Psychological Distress in Chinese Nurses

Abstract: Background: A high prevalence of psychological distress is observed in nurses due to multiple occupational stressors. Personality traits and personal factors are important factors that lead to psychological distress. The personality profile reflects a combination of personality traits; however, the relationship between personality profiles and personal factors that affect psychological distress among nurses has not been defined. Methods: This cross-sectional study was conducted in November 2020 in China. Conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 75 publications
2
19
0
Order By: Relevance
“…First, the WPV-PMTP has an effect on the improvement of occupational coping self-efficacy. Indeed, studies have found support for the notion that the impact of job-related psychological distress may be associated with low coping self-efficacy [ 43 , 47 , 68 ]. Nurses’ perceived occupational coping self-efficacy may not only be a capacity, but also a specific functioning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the WPV-PMTP has an effect on the improvement of occupational coping self-efficacy. Indeed, studies have found support for the notion that the impact of job-related psychological distress may be associated with low coping self-efficacy [ 43 , 47 , 68 ]. Nurses’ perceived occupational coping self-efficacy may not only be a capacity, but also a specific functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The total scores were summed with a higher score indicating stronger beliefs regarding how confident nurses feel they can cope with occupational stressful situations and actively address challenges. The Cronbach’s α of 0.930 was high [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many nurses can continue to provide high-quality care and have satisfactory careers despite the multiple challenges of the current medical environment, which is consequenced by the diverse responses of individuals to stressors ( Mark and Smith, 2012 ). As a result, great interest is in the positive traits and psychological resources that may help nurses cope with the challenges in work, such as self-efficacy, hope, optimism, resilience, and grit ( Young and Rushton, 2017 ; Zhou et al, 2017 ; Meyer et al, 2020 ; Huang et al, 2021 ), increasing those resources may help reduce clinical nurses’ vulnerability to psychological distress ( Hjemdal et al, 2006 ; Abraham et al, 2021 ). Among these, grit and hope may have such effects and mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the factors listed above, the personality makeup of the doctor also plays an important role [ 39 ]. A doctor who is emotionally stable and agreeable in interaction is likely to better manage these challenges of professional life [ 40 ]. Empathy, modesty, altruism and compassion are personality traits that play a major role in medical practice [ 41 ].…”
Section: Introductionmentioning
confidence: 99%